“Bioactive primers”- macroshield against micro-leakage in restorative dentistry? - Gurucharan, Ishwarya; Balasubramanian, Saravanakarthikeyan; Sekar, Mahalaxmi (Journal of Orofacial Research, 2020)
In today’s dental era, minimal intervention dentistry is widely recommended to conserve maximal sound tooth structure by careful removal of only caries infected dentin. However, residual bacteria which remain in dentinal tubules of relatively healthy part of dentin make it impossible to achieve a complete caries free environment. This brief commentary will highlight on the recent advancements in adhesive resin composites with significant antibacterial effects which may aid in effective restoration of such cavities.